Priors from general equilibrium models for VARs - Marco Del Negro; Frank Schorfheide (Federal Reserve Bank of Atlanta, 2002)
This paper uses a simple New Keynesian monetary DSGE model as a prior for a vector autoregression and shows that the resulting model is competitive with standard benchmarks in terms of forecasting and can be used for policy analysis.
Keywords: 330; Forecasting; Vector autoregression